Thermodynamics of pyrope-majorite, Mg3Al2Si3O12-Mg4Si4O12, solid solution from atomistic model calculations - Gale, Julian; Vinograd, V.; Winkler, B.; Putnis, A.; Kroll, H.; Milman, V.; Fabrichnayak, O. (Taylor & Francis Ltd, 2006)
Static lattice energy calculations, based on empirical pair potentials have been performed for a large set of different structures with compositions between pyrope and majorite, and with different states of order of octahedral cations. The energies have been cluster expanded using pair and quaternary terms. The derived ordering constants have been used to constrain Monte Carlo simulations of temperature-dependent properties in the ranges of 1073 3673K and 0 20 GPa. The free energies of mixing have been calculated using the method of thermodynamic integration. At zero pressure the cubic/tetragonal transition is predicted for pure majorite at 3300 K. The transition temperature decreases with the increase of the pyrope mole fraction. A miscibility gap associated with the transition starts to develop at about 2000K and xmaj 0.8, and widens with the decrease in temperature and the increase in pressure. Activity composition relations in the range of 0 20 GPa and 1073 2673K are described with the help of a high-order Redlich Kister polynomial.